2017
DOI: 10.1167/iovs.17-21572
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of HCN Channel Block on On and Off Pathways in the Retina as a Potential Cause for Medication-Induced Phosphene Perception

Abstract: Our data suggest that pharmacologic HCN channel block in the retina leads to a shift in the relative activity of the On and Off pathways of the retina. We hypothesize that this imbalance may underlie the medication-induced perception of phosphenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 69 publications
0
7
0
10
Order By: Relevance
“…The observed ON/OFF imbalance may account for the visual symptoms commonly associated with abrupt changes in light intensity seen in ivabradine treated patients (Borer et al, 2003;Cervetto et al, 2007). Similar suggestion was made by Bemme et al (2017), who demonstrated that ivabradine differentially affects the activity of the ON and OFF ganglion cells in mouse retina. The ON cells showed reduced response gain, whereas OFF cells experienced an increase in response threshold under temporal white noise stimulation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The observed ON/OFF imbalance may account for the visual symptoms commonly associated with abrupt changes in light intensity seen in ivabradine treated patients (Borer et al, 2003;Cervetto et al, 2007). Similar suggestion was made by Bemme et al (2017), who demonstrated that ivabradine differentially affects the activity of the ON and OFF ganglion cells in mouse retina. The ON cells showed reduced response gain, whereas OFF cells experienced an increase in response threshold under temporal white noise stimulation.…”
Section: Discussionmentioning
confidence: 56%
“…We chose concentration of 75 μM ZD7288, because it had saturating effect for both the b-and d-wave amplitude changes. Ivabradine was used in a concentration of 30 μM on the basis of our preliminary experiments, where concentrations of 3, 30 and 60 μM were tested in accordance with other retinal studies: 3 μM (Della Santina et al, 2012;Bemme et al, 2017), 30 μM (Demontis et al, 2009).…”
Section: Subjects and Drug Applicationmentioning
confidence: 99%
“…HCN currents are critical for rhythmic activities in the heart pacemaker cells and neurons in the central nervous system (Baker et al, 1997 ; Day et al, 2005 ; Knop et al, 2008 ). In contrast, in the retina HCN channels have been associated with transient signaling as well as higher-frequency tuning (Cangiano et al, 2007 ; Della Santina et al, 2012 ; Puthussery et al, 2013 ; Bemme et al, 2017 ). These results suggest that HCN currents shape the high-frequency responses.…”
Section: Discussionmentioning
confidence: 99%
“…Neben Messungen von Elektroretinogrammen (ERGs) an lebenden Versuchstieren (Della Santina et al 2010) konnte ein ähnliches Ergebnis auch an Knock-Out-Modellen mit gentechnisch "ausgeschalteten" HCN1-und HCN2-Kanälen erhoben werden (Della Santina et al 2012;Knop et al 2008;Seeliger et al 2011). Kürzlich wurden zudem Auswirkungen einer HCN-Kanal-Inhibition auf die Ganglienzellen nachgewiesen, deren Aktivität und Antwortreaktion auf Lichtreize durch Ivabradin verändert wurden (Bemme et al 2017). Diese Befunde untermauern die Bedeutung des Ih-Ionenstroms für die Informationsverarbeitung in der Netzhaut und lassen einen Zusammenhang zu den visuellen Nebenwirkungen bei medikamentöser Anwendung von Ivabradin erkennen.…”
Section: Abkürzungsverzeichnisunclassified
“…In einer aktuell veröffentlichten Studie wurde der Effekt von Ivabradin auf die Ganglienzellsignale untersucht, deren Antwortverhalten sich durch die HCN-Kanalblockade veränderte (Bemme et al 2017). Bei den ON-Ganglienzellen nahm die Spontanaktivität zu, während die Spontanaktivität der OFF-Ganglienzellen sich insgesamt reduzierte und salvenartig auftrat.…”
Section: Hcn-kanäle In Der Retina Und Ihr Einfluss Auf Die Zellsignaleunclassified